RAGAM KAJIAN GENDER DI KALANGAN MAHASISWA SEKOLAH TINGGI AGAMA ISLAM NEGERI (STAIN) PAMEKASAN - Siti Musawwamah (Karsa: Journal of Social and Islamic Culture, 2015)
The differences of understanding and point of view on gender and gender equity have become the basis of this study. It exploits the distinction any further particularly in academic community. The focus of study is specifically on the orientation of research theme and the direction of gender study analysis which are written by in undergraduate thesis. The study is successful in identification that gender study themes have been dominated by the contextual study or ap-licative-empiric instead of the study of textual or normative-legalistic. Gender study is viewed as the study about women not about gender or the study utili-zing gender as tool of analysis. The analysis of women study mostly use des-criptive one, it only describes position and role of women, whereas the gender study uses critical analysis, that ilustrate the arguments behind the role and position of women. It could be identified wether the position and role of women  are equal or not wiht men.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i1.612